Synthesis of Methyl 2-[Bis(benzylthio)phosphoryl]acetate as a Novel Horner–Wadsworth–Emmons-Type Reagent and Its Application to the Diastereodivergent Synthesis of (E)- and (Z)-α,β-Unsaturated Esters - Sano, Shigeki; Yamada, Shoki; Ihara, Takahito; Seki, Kazumasa; Kitaike, Syuji; Nakao, Michiyasu (Synlett, 2024)
Methyl 2-[bis(benzylthio)phosphoryl]acetate has proven to be an efficient Horner–Wadsworth–Emmons (HWE)-type reagent for the diastereodivergent synthesis of (E)- and (Z)-α,β-unsaturated esters. Under the conditions of excess NaHMDS relative to the HWE-type reagent, the HWE-type reactions of methyl 2-[bis(benzylthio)phosphoryl]acetate with various aldehydes afforded the corresponding α,β-unsaturated esters in an E-selective manner in up to 100:0 E/Z ratio. However, when an excess of the HWE-type reagent was used relative to NaHMDS, the stereoselectivity of the HWE-type reactions was dramatically changed from E to Z, yielding an E/Z ratio of up to 2:98.
Keywords: Horner–Wadsworth–Emmons reagent; phosphorus–sulfur bond; α,β-unsaturated esters; diastereodivergent synthesis; olefination; aldehydes